Empirical investigation into the applicability of surrogacy for juvenile salmonids (Oncorrhynchus spp.) exposed to hydropower induced rapid decompression - Bernardo Beirão (Elsevier, 2021)
Surrogacy, whereby the response of a representative species subjected to a stressor is applied to one or more species, is commonly used without validation in conservation research and applications. The objective of this study was to empirically evaluate the appropriateness of using morphologically and phylogenetically similar species as surrogates for laboratory experiments that develop dose–response relationships for rapid decompression. In this study, juvenile kokanee, rainbow trout, and Chinook salmon were evaluated for injuries after exposure to rapid decompression that simulated pressure time-histories that are representative of hydropower turbine passage. Dose-response relationships, which modeled probability of mortal injury as a function of rapid decompression, were constructed for each species and compared to determine if differences existed between species across the range of rapid decompression. The surrogacy potential of these three species was also evaluated by incorporating the dose–response curves into the Biological Performance Assessment (BioPA) tool to predict the probability of adverse passage as a function of mortal injury and LRP exposure probabilities during three common operation scenarios of a computational fluid dynamics modeled Kaplan turbine (lower 1% generation limit, peak generation, and upper 1% generation limit). Although dose–response curves differed among species, the differences occurred at more extreme decompression values which had a low probability of occurring under the three Kaplan turbine operation scenarios tested using the BioPA tool. Therefore, the three species had similar BioPA scores for adverse passage probabilities, indicating they could act as surrogates for one another under certain (i.e., low LRP) passage conditions.